2010
DOI: 10.1080/00071668.2010.503477
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and response of intestinal microflora and mucins to manno-oligosaccharide and antibiotic supplementation in broiler chickens

Abstract: 1. An experiment was conducted to characterise and evaluate, in comparison to zinc bacitracin (ZnB), the response of intestinal microflora and mucins to manno-oligosacchares (MOS, Bio-MOS(R), Alltech Biotechnology, Nicholasville, Kentucky, USA). 2. Supplementation of MOS and ZnB selectively increased the intensity of sulphomucins. As revealed by the plate culture method, MOS accelerated the maturation of gut microflora by promoting the growth of lactobacilli in the ileal mucosa and vice versa on ileal and caec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 43 publications
2
42
1
Order By: Relevance
“…It is known that diet modulates the monosaccharide composition of mucin carbohydrate side chains (Sharma et al, 1997;Fernandez et al, 2000;Jamroz et al, 2006;Chee et al, 2010a and2010b). Research so far has examined the effect of dietary components such as amino acids, that is, threonine (Chee et al, 2010b), probiotics (Smirnov et al, 2005), prebiotics (Chee et al, 2010a and2010b) and antibiotics (Smirnov et al, 2005;Chee et al, 2010a) in intestinal mucin dynamics of poultry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that diet modulates the monosaccharide composition of mucin carbohydrate side chains (Sharma et al, 1997;Fernandez et al, 2000;Jamroz et al, 2006;Chee et al, 2010a and2010b). Research so far has examined the effect of dietary components such as amino acids, that is, threonine (Chee et al, 2010b), probiotics (Smirnov et al, 2005), prebiotics (Chee et al, 2010a and2010b) and antibiotics (Smirnov et al, 2005;Chee et al, 2010a) in intestinal mucin dynamics of poultry.…”
Section: Discussionmentioning
confidence: 99%
“…Research so far has examined the effect of dietary components such as amino acids, that is, threonine (Chee et al, 2010b), probiotics (Smirnov et al, 2005), prebiotics (Chee et al, 2010a and2010b) and antibiotics (Smirnov et al, 2005;Chee et al, 2010a) in intestinal mucin dynamics of poultry. Jamroz et al (2006) studied the effect of PFA in broiler diet, which resulted in a higher mucus secretion in gastric and jejunal villi in 42-day-old broilers fed diet supplemented with plant extract containing carvacrol, cinnamaldehyde and capsicum oleoresin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of dietary antimicrobials on the mucosa-associated bacteria is relatively limited. Recently, Chee et al (2010) have reported that antibiotic treatment affected the number of lactobacilli in digesta of the ileum, but not on the mucosa.…”
Section: Effect Of Antimicrobials On Gut Microbiota Communitymentioning
confidence: 99%